Non-invasive evaluation of the liver disease severity in children with chronic viral hepatitis using FibroTest and ActiTest – comparison with histopathological assessment - Pokorska-Śpiewak, Maria; Kowalik-Mikołajewska, Barbara; Aniszewska, Małgorzata; Pluta, Magdalena; Marczyńska, Magdalena (Clinical and Experimental Hepatology, 2017)
Aim of the study was to evaluate liver disease severity in children with chronic viral hepatitis using the FibroTest and ActiTest (FT/AT), and compare the results with the liver biopsy. Material and methods: The study included 11 treatment-naïve children [mean age, 9.0 ± 3.0 years, 10 infected with hepatitis C virus (HCV), and 1 with hepatitis B virus (HBV)] who underwent an FT/AT. Ten of the children underwent a liver biopsy. The histopathological evaluation was based on the METAVIR scoring system. The FT/AT and METAVIR scores were considered concordant if the necroinflammatory activity or the fibrosis did not differ by more than one grade or stage. To analyze the agreement between the FT/AT and the histopathological evaluation, the inter-rater agreement (kappa) was used. Results : In the histopathological evaluation, most children presented with mild necroinflammatory activity (METAVIR A1) and with minimal to mild fibrosis (METAVIR F1-2). Both the AT and FT values did not show any linear increases with advancing METAVIR scores A and F, respectively. A discordance between the FT and METAVIR scores was observed in 3/10 (30%) cases; concordance between the AT and METAVIR scores was found in 9/10 cases. The inter-rater agreement test showed poor agreement between the FT/AT and the histopathological evaluation (kappa for AT: 0.0667, and kappa for FT: 0.176). Conclusions : The FT and AT values poorly correlate with histopathological evaluation. Further studies on non-invasive methods to evaluate liver disease severity in children with chronic viral hepatitis are needed.